(untitled) (Biological Sciences - PJSIR, 2001)
A study was planned to prepare whole soymilk using two different methods from the indigenous soybean. The extraction of soymilk was carried out from whole soybean and dehulled soybean. The soymilk samples thus prepared were then analyzed and their quality of protein were evaluated by conducting 10 days feeding trial at 10% protein level to weanling albino rats. Skim milk (standard protein), cerelac of wheat (for comparison) and non-protein diets were also involved in feeding trial. Proximate analysis revealed that dehulled soybean milk is more nutritious as compared to whole soybean milk. The data on feeding trial showed Protein Efficiency Ratio (PER) 26,1.7; True Digestibility (TD) 90.0,88.0; Net Protein Utilization (NPU) 69.0,58.0 and Biological Value (BY) 77,66 for dehulled soymilk and whole soymilk respectively. Where as for skim milk and cerelac (wheat) PER 2.8,3.1; TD 92,92; NPU 74,66 and BV 81,71 respectively. Based upon the above results it is suggested that soymilk may be prepared on large scale from dehulled soybean and may be used as supplement food for children and population at risk.